Photoconductivity and laser operated piezoelectricity the Ag-Ga-Ge-(S, Se) crystals and solid solutions. (1st November 2018) - El-Naggar, A.M.; Albassam, A.A.; Myronchuk, G.L.; Zamuruyeva, O.V.; Kityk, I.V.; Rakus, P.; Parasyuk, O.V.; Jędryka, J.; Pavlyuk, V.; Piasecki, M.
Abstract: A new type of chalcogenide semiconductors possessing different laser operated optoelectronic features is studied for the AgGaGeS4 –AgGaGe3 Se8 crystalline system give a rare opportunity to form continuous solid solution series based on the substrate compounds. This one allow to perform efficient operation by their optical and electronic features using an external laser light due to presence of huge number of intrinsic defects and high electron-phonon anharmonicities [1] . With accordance to previously reported method were prepared specimens of high quality and homogenous in centimeter range (confirmed by SEM and EPMA) AgGaGeS4 and AgGaGe3 Se8 single crystals and the series of intermediate solid solution, in particular AgGaGe1.8 S2.4 Se3.2, AgGaGe2 S2 Se4 and AgGaGe2.2 S1.6 Se4.8 . The investigated Ag-Ga-Ge-(S, Se) crystals and solid solutions posses high non-linear optical efficiencies as well as high birefringence that make them efficient for coherent laser frequency conversion in the near-infrared spectral range. So they may be promising for the coherent laser frequency convertors. To expand the possibilities of applications as pressure sensors, optical triggers, modulators or radiation detectors and for better understanding of relation between composition-structure-properties for these materials we perform the complex investigation of temperature dependences of the transparency, photoconductivity, rise and decreasing photocurrent relaxation for determination parameters of localized states and temperature dependent, photoinduced piezoelectric properties.